Implementation of Bandwidth Management Authentication - Aulia Rahman; Haviluddin Haviluddin (International Journal of Computing and Informatics (IJCANDI), 2016)
An internet traffic service mechanism includes monitoring and network security is indispensable. The main purpose of network monitoring is bandwidth optimizing and maintaining network security. This paper has described and implemented Remote Authentication Dial-In User Service (RADIUS) protocol and Authentication, Authorization and Accounting (AAA) server integrated with Mikrotik. The purpose of this article deal with the implementation of bandwidth management, which includes LAN (Local Area Network) and Wi-Fi (Wireless Fidelity) in Universitas Mulawarman. Based on experiment, the system is simple and easy to be used that controls and allocates bandwidth to users (lecturers, staff, and students) as they authenticate with LAN and Wi-Fi. Furthermore, network security perspective shows that users who are not registered to use the internet at the Universitas Mulawarman could be maintained as well.